Professional communications OER : Modules 1-4 : overiew - Olds College OER Development Team; BC Open Textbook Project; BCcampus (Olds College, 2017)
"This Open Educational Resource (OER), developed by Olds College is collaboration with the Government of Alberta, is a series of modules intended for use in Higher Education courses or by independent learners. This resource is useful for instructors whose courses cover introductory communication skills, workplace communication, technical communication, or business writing. It contains four modules (Foundations, Writing, Presentations, and Interpersonal), each with its own lesson plans, assessments, and supporting materials. Below, you will find online access to the entire series, plus an instructor overview of the modules. For the PDF and editable files, and instructor resources for each individual module, select the FIND links below"--BC Campus website.
Module 1. Foundations -- Module 2. Writing -- Module 3. Presentations -- Module 4. Interpersonal.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online version; Title from PDF (viewed on June 20, 2017)
Keywords: Business writing -- Textbooks; Communication of technical information -- Textbooks; Communication -- Textbooks; Electronic books